Pengembangan bahan ajar dengan menggunakan pendekatan kontekstual berbantuan liveworksheet pada materi statistika - Siti Bunga Alifiya; Jozua Sabandar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Â This study aims to develop teaching materials using a contextual approach assisted by liveworksheets on statistical material. The research method used in this research is the R&D (Research and Development) method using the 4D model which is limited to step 3 namely define, design, develop. The instruments in this study were in the form of non-tests and written tests in the form of student response questionnaires with a total of 25 questions and 5 written test questions according to the steps of the contextual approach. The subjects of this study were class VIII students at one of the junior high schools in the Batujajar District with a sample of 30 class VIII students as respondents for the level of product effectiveness. The results of this study are that the teaching materials developed are declared valid and suitable for use, this is in accordance with the results of the validation of experts, as well as getting a positive response from students. So the teaching materials developed are good for use during the learning process of mathematics.